Armies of peace : Canada and the UNRRA years - Armstrong-Reid, Susan, 1950- (University of Toronto Press, 2008)
Armies of Peace is the first comprehensive investigation of Canadians' influence on the establishment and operation of The United Nations Relief and Rehabilitation Administration (UNRRA).